Social and Governance Changes: Rate, Principles and Morals - Nardo , Massimo N.; Francis , Ronald D. (Journal of Law and Governance, 2013)
This paper draws attention to two aspects of change; first, the rate of social change is a source of concern, to this is added that both the configuration of changes and the values dimension, add to those concerns. Change makes it hard to keep up, and is the generator of much stress. We need to apprehend that such a point applies strongly to all enterprises, in particular to governance issues. This article holds that the rate of change is compounded by a constantly changing configuration. To ameliorate those concerns it is held that there needs to be both an expression of agreed basic principles, and recognition that values are one of the most vital parts of that selection. In this the debate and explication of guiding principles, particularly in governance, that is crucial. The main point here is to again emphasise the complexity that results not only from the rate of change but also the configuration and moral values that it constantly tests. It is only by direct consideration that concern over such issues be reduced. It is also held that an explication of basic principles is a significant aid to coping with the source of such stress.